The Effect of Multi-Generational Selection in Geometric Semantic Genetic Programming - Castelli, Mauro (2022)
Castelli, M., Manzoni, L., Mariot, L., Menara, G., & Pietropolli, G. (2022). The Effect of Multi-Generational Selection in Geometric Semantic Genetic Programming. Applied Sciences (Switzerland), 12(10), 1-13. https://doi.org/10.3390/app12104836 --------- Funding: This work was supported by national funds through the FCT (Fundação para a Ciência e a Tecnologia) by the projects GADgET (DSAIPA/DS/0022/2018).